The Interaction Between Brand Image, Brand Attachment and Brand Loyalty in Green Branding Context: The Mediating Role of Customer Engagement - Yaran Ögel, İlkin (Journal of Applied And Theoretical Social Sciences, 2021)
As environmental problems are dramatically alarming the world, environmental issues have become the primary concerns of both consumers and companies. To please the environmental wants of consumers, many companies have to adopt green solutions today. Green brands are one of these solutions. Nevertheless, little has been known about the green brands. In this sense, this study attempts to explore the interaction between brand image (BIm), brand attachment (BAtt), customer engagement (CEn) and brand loyalty (BLo) within the scope of green brands as previously untapped context. In this study while brand image is determined as independent variable; customer engagement is specified as the mediator variable which mediates the link between brand image and brand attachment. Data were gathered from 428 participants through convenience sampling method. To examine the links between the variables in the suggested model, structural equation modelling was utilized. The results regarding the study bring out that brand image for green brands significantly influences customer engagement and brand attachment in a positive way; customer engagement has also a significant positive influence on brand attachment for green brands; and brand attachment for green brands significantly affects brand loyalty toward these brands in a positive way. In addition, partial mediating influence of customer engagement on the link between brand image for green brands and brand attachment was found significant. These findings also ensure applicable insights to practitioners, who are responsible for promotion of green brands, by emphasizing the importance of increasing brand image, customer engagement and customer attachment to generate loyal green customers.